SURFACE STRESS EFFECT IN MECHANICS OF NANOSTRUCTURED MATERIALS - Wang, Jianxiang; Huang, Zhuping; Duan, Huiling; Yu, Shouwen; Feng, Xiqiao; Wang, Gangfeng; Zhang, Weixu; Wang, Tiejun (Acta mechanica solida Sinica, 2011)
This review article summarizes the advances in the surface stress effect in mechanics of nanostructured elements, including nanoparticles, nanowires, nanobeams, and nanofilms, and heterogeneous materials containing nanoscale inhomogeneities. It begins with the fundamental formulations of surface mechanics of solids, including the definition of surface stress as a surface excess quantity, the surface constitutive relations, and the surface equilibrium equations. Then, it depicts some theoretical and experimental studies of the mechanical properties of nanostructured elements, as well as the static and dynamic behaviour of cantilever sensors caused by the surface stress which is influenced by adsorption. Afterwards, the article gives a summary of the analytical elasto-static and dynamic solutions of a single as well as multiple inhomogeneities embedded in a matrix with the interface stress prevailing. The effect of surface elasticity on the diffraction of elastic waves is elucidated. Due to the difficulties in the analytical solution of inhomogeneities of complex shapes and configurations, finite element approaches have been developed for heterogeneous materials with the surface stress. Surface stress and surface energy are inherently related to crack propagation and the stress field in the vicinity of crack tips. The solutions of crack problems taking into account surface stress effects are also included. Predicting the effective elastic and plastic responses of heterogeneous materials while taking into account surface and interface stresses has received much attention. The advances in this topic are inevitably delineated. Mechanics of rough surfaces appears to deserve special attention due to its theoretical and practical implications. Some most recent work is reviewed. Finally, some challenges are pointed out. They include the characterization of surfaces and interfaces of real nanomaterials, experimental measurements and verification of mechanical parameters of complex surfaces, and the effects of the physical and chemical processes on the surface properties, etc.